The Portrayal of Systemic Racism in Carlos López Estrada’s Script in Blindspotting Movie - Revone, Junita; Yulistiyanti, Yulistiyanti (Humanitatis : Journal of Language and Literature, 2024)
This research highlights the issue of systemic racism portrayed in Blindspotting movie, through the experiences of Collin as the black American character. The aims of this research are (1) to reveal what forms of systemic racism exist; (2) to identify the factors that cause systemic racism in the movie; and (3) to find out how systemic racism affects the main character’s life in the movie. Qualitative descriptive methods are applied for this research. By using a sociological approach as the theoretical framework of this research, Joe R. Feagin's theory of systemic racism is applied to analyze the issue of systemic racism in the movie. The result shows that through this movie, research also found that historical roots and the white racial frame are the factors causing systemic racism. There are several forms of systemic racism experienced by Collin, including: (1) police brutality and racial profiling; (2) racial bias in the criminal justice system; (3) racial stereotypes and microaggressions; and (4) gentrification. This research also found that the historical roots of racism and the white racial frame are the factors causing systemic racism. As a result of systemic racism, Collin's life is affected both from a social and psychological aspect. Keywords: systemic racism, sociology of literature, police brutality, racial stereotypes, microaggressions, gentrification.